Prevalence and risk factors of postpartum depression and anxiety after covid-19 pandemic: a systematic review - Lee, Shi En (2024)
Background and Objective: Postpartum depression (PPD) is a harmful mental health condition that may affect the person’s thoughts and behavior. It may be experienced by the mother after giving childbirth. Many of these studies were conducted during the COVID-19 lockdown which could be one of the possible confounding factors. There have been no systematic reviews conducted in journals pertaining to this topic after the COVID-19 lockdown. This systematic review primarily aims to collate and critically analyze research studies on the prevalence and risk factors of postpartum depression and anxiety.